Experimental investigation of the protein foam flow structure in horizontal channels:Flow regime and corresponding bubble size distribution - Zoheidi, Ladan; Panradl, Christian; Rauh, Cornelia; Delgado, Antonio (Journal of Food Process Engineering, 2017)
The present study offers the flow patterns and associated structure of protein foam flowing in a horizontal channel. An experimental equipment was developed to study the protein foam flow regime and the related bubble size distribution. The foam formation was performed with the help of a foam generator and transported in a horizontal channel. The optical measurements were performed by a high speed camera which enabled the foam flow visualization at the channel wall. The foam flow pattern and the corresponding bubble size distribution were studied as a function of the foam quality. As a consequence of the higher drainage and gravitational effect at higher gas flowrates, the foam structure resulted in different flow patterns. The bubble size distribution was studied as a function of the volumetric gas and liquid flowrate. The foam consisting of bubbles on the millimeter scale showed a close fit to the log‐normal distribution. Practical applications One of the most important attributes of the two‐phase flow is the bubble structure resulting in different foam flow regimes. Since the final appearance of foam food products and their textural properties such as their smoothness are associated with the foam uniform distribution of the bubbles, the main objective of the present work is given to provide the first experimental results of the milk protein foam flow regime and corresponding bubble sizes during mechanical transport through a horizontal duct.
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.flowre